Community Empowerment Through Environmental Care and Disaster Relief Programs at Zakat House in Bintaro, Tanggerang Selatan - Ulzana, Nazhmia (Al Khidma: Jurnal Pengabdian Masyarakat, 2024)
In Islam, zakat is an act of worship to purify, cleanse the heart, for Allah SWT. In Indonesia, there is an institution, namely Rumah Zakat, an institution that helps community empowerment. Rumah Zakat is a national amil zakat institution belonging to the people of Indonesia which manages zakat, infaq, alms, and other humanitarian funds through a series of integrated programs in the fields of education, health, economy and the environment, to create happiness for people in need. Of the many programs in certain fields, we focus on the disaster sector. In the field of disaster, it is very interesting for us to discuss, because the country of Indonesia experiences disasters almost every year, especially floods, landslides, earthquakes, volcanic eruptions, etc. And the many natural disasters that occurred caused Indonesia to lose hundreds of thousands of lives. The most important thing is that this zakat house has a form program in it to develop the community and help the community. With this program, the institution donates funds in the form of money or goods to the people affected by the disaster. As a form of community empowerment, we as researchers conducted research on the zakat house. The forms of these programs include emergency response programs, pre-disaster programs, community programs that receive clean water, and programs such as the community obtaining plant seeds for reforestation. This study aims to find out what forms of programs are carried out by zakat houses for people affected by floods. We as researchers use qualitative research. The method we use is like observation through the media. With this activity, researchers want to know the work process of the program and what impact it will have on the community. And in the results we found that the community was happy with the participation of an institution that was responsible for managing the disaster that occurred. We hope as writers that this institution will increase in the process of community empowerment on the basis of environmental disaster.